Primary vaginal endodermal sinus tumor in infants and children: experience from a tertiary center - Min Yin; Jiaxin Yang; Tao Wang; Sijian Li; Xinyue Zhang (BMC, 2022)
Abstract Background The objective of the study was to analyze the clinical features, treatment, and outcomes of primary vaginal endodermal sinus tumor (EST) in infants and children treated in a tertiary center. Methods Clinical data of patients with pathologically confirmed primary vaginal EST in our hospital from January 1997 to December 2017 were retrospectively reviewed and analyzed. Results A total of 21 patients were included in this study. The median age at diagnosis was 11 months (range, 4-44 months). The most common manifestations were abnormal vaginal bleeding, and a polypoid mass protruding from the vagina. Chemotherapy based on PEB (cisplatin, etoposide, bleomycin) regimen was given, and serum alpha-fetoprotein (AFP) levels dropped to normal levels after 2 to 4 cycles of chemotherapy (median, 2 cycles). After 3 to 13 cycles of chemotherapy, with a median of 5 cycles, 20 patients achieved complete remission (95.2%). The median follow-up time was 80 months (range, 4-281months). At the time of the last follow-up, 19 cases were alive without disease, and the survival rate was 90.5%. Conclusion Vaginal EST is a very rare malignant germ cell tumor and is sensitive to chemotherapy. Conservative surgery combined with PEB chemotherapy is an effective way of treatment. Serum AFP and imaging examinations can monitor the treatment response and recurrence.